Effect of porous density of twisted tape inserts on heat transfer performance inside a closed conduit - Rahman, Md Tauhidur; Habib, Khairul; Quader, Md Niamul; Aslfattahi, Navid; Kadirgama, Kumaran; Das, Likhan (Elsevier Ltd, 2023)
This study examines the impact of varying the porosity density of twisted tape inserts (TTI) on the temperature distribution, fluid velocities, heat transfer coefficients (HTC), Nusselt numbers (Nu), turbulent kinetic energy (TKE), and performance from 5000 to 12500 Reynolds numbers (Re). The entire process involved the design of TTIs and double pipe heat exchangers using SolidWorks. Subsequently, a three-dimensional fluid flow model was employed to solve equations related to energy mass, energy, and momentum within the ANSYS Fluent interfaces. The findings highlight the noteworthy impact of high porosity TTIs, which consistently reduce temperature spans, increase fluid velocities, and greatly HTC and Nu when compared to low porosity TTI, typical TTI, and plain tubes. Furthermore, high porosity TTI significantly increases TKE, indicating increased fluid turbulence and higher heat transfer efficiency, especially at Re = 12500. The assessment of PEC emphasizes the superiority of high porosity TTI, demonstrating their significant performance increase potential of over 6.44 % over low porosity TTI and a staggering 62.5 % above typical TTI. In conclusion, high porosity TTI emerges as a potential solution for improving heat transfer efficiency and overall system performance in a variety of industrial applications, promising enhanced energy efficiency and superior performance.